2019
DOI: 10.1002/ptr.6377
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ginger (Zingiber officinale) on chemotherapy‐induced nausea and vomiting in breast cancer patients: A systematic literature review of randomized controlled trials

Abstract: Breast cancer is the most commonly diagnosed cancer and is the leading cause of mortality due to all types of cancers among the female population worldwide. Results of clinical trials investigating the effect of ginger on chemotherapy-induced nausea and vomiting (CINV) in breast cancer patients are inconsistent. This study was aimed at obtaining a comprehensive overview of the current evidence regarding the effectiveness of ginger as an antiemetic modality for controlling CINV in breast cancer patients. All pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…The data of Panahi et al study in 2012, showed no significant difference between the intervention and control groups in each of the four subclasses of severity of acute and delayed nausea (4) . Another three studies did not support the effect of ginger in reducing the severity of nausea (Ansari et al2016;Thamlikitkul et al2017;Li et al2018) (14,13,1,19) ,on the contrary to these studies, our study showed that the differences in severity of acute and delayed nausea between both study groups were statistically significant.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The data of Panahi et al study in 2012, showed no significant difference between the intervention and control groups in each of the four subclasses of severity of acute and delayed nausea (4) . Another three studies did not support the effect of ginger in reducing the severity of nausea (Ansari et al2016;Thamlikitkul et al2017;Li et al2018) (14,13,1,19) ,on the contrary to these studies, our study showed that the differences in severity of acute and delayed nausea between both study groups were statistically significant.…”
Section: Discussioncontrasting
confidence: 96%
“…Five studies showed this result too by finding that ginger intake had no significant effect in controlling acute and delayed vomiting (Li et al2018 (1,13,14,15,4) , but all the previous studies including this study disagreed with what had been concluded by (Arslan et al2015;Yekta et al2012) that ginger had significant effect on chemotherapy induced vomiting (16,17) .This might be due to that in our study the intervention with ginger was after chemotherapy. Ryan et al speculated that using ginger before chemotherapy may prepare the intestine for emetic response by binding to 5-HT3 receptors which may give better results (18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Ginger had been investigated as an additional or alternative treatment to standard regimens in fifteen clinical trials of CINV, but the results between studies were controversial, with only about half of them demonstrating significant effects corresponding to the results of previous systematic reviews [73,74]. Moreover, studies from Yunes et al and Müzeyyen et al, where they concluded the antiemetic effect of ginger, were assessed to have a high risk of bias in the blinding of participants [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Since many review articles, including systematic reviews and meta‐analyses, have been recently published on the antiemetic properties of ginger (Chang & Peng, 2019; Crichton, Marshall, Marx, McCarthy, & Isenring, 2019; Saneei Totmaj, Emamat, Jarrahi, & Zarrati, 2019), the present article will focus on ginger analgesic, antiinflammatory, and metabolic (antidiabetic and hypolipidemic) actions. Information on the potential use of ginger in other ailments, such as gastrointestinal diseases, cancer, and hypertension can be found elsewhere (de Lima et al, 2018; Hasani et al, 2019; Mahomoodally et al, 2019; Nikkhah Bodagh, Maleki, & Hekmatdoost, 2019; Saneei Totmaj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%